Religious Moderation in Indonesia - Imron Bima Saputra; Fachruddin Azmi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2022)
Moderation is a core tenet of Islam. Moderate Islam is a religious understanding that is very relevant in the context of diversity in all aspects, both religion, customs, ethnicity and the nation itself. Educational institutions have a strategic role to break the chain of violence in the name of religion. An educational approach for all students that can be implemented in peace education which is integrated with the school curriculum. Thus, religious moderation is very necessary to be instilled in students in order to create a harmonious relationship between teachers, students, the community and the surrounding environment so as to create a peaceful and safe environment. of various threats to a peaceful Indonesia. This research is a research that uses qualitative research methods, where the research method describes and describes matters relating to Religious Moderation in Indonesia. Researchers describe and describe the data from the opinions of experts. It is hoped that this qualitative method will allow the research to comprehensively explain the facts regarding Religious Moderation in Indonesia.